Real-world cardiovascular risks of ibrutinib in chronic lymphocytic leukemia: a retrospective study - Ivanovic, Jelena; Otasevic, Vladimir; Markovic, Ksenija; Vukovic, Vojin; Bibic, Tamara; Tomic Vujovic, Kristina; Kozarac, Sofija; Vladicic Masic, Jelena; Milic, Natasa; Kulic, Jovan; Antic, Darko (Frontiers in Oncology, 2025)
IntroductionIbrutinib has made significant contributions to the treatment of chronic lymphocytic leukemia (CLL) with recognized cardiovascular toxicities in some patients. This study aimed to assess the incidence of cardiotoxicity in CLL patients treated with ibrutinib and identify associated risk factors.MethodsThis retrospective cohort study analyzed 79 CLL patients treated with ibrutinib at the University Clinical Center of Serbia. Patient characteristics, treatment outcomes, and cardiovascular events were analyzed to determine the incidence of cardiotoxicity and its potential predictors.ResultsThe median age at diagnosis was 58 years, with 63.3% male patients. Pre-existing cardiovascular conditions were present in 55.7% of patients. Cardiotoxicity occurred in 29.1% of patients, with atrial fibrilation developing in 10.1% patients (37.5% grade 3), leading to therapy discontinuation in 62.5% of those affected. Also, we diagnosed hypertension in 15.2%, heart failure in 7.6%, and myocardial infarction in 2.5% of patients. Furthermore, one case (1.3%) of sudden cardiac death was recorded. The administration of ibrutinib was ceased in 9 patients due to cardiotoxic effects. Patients with prior cardiovascular disease had a threefold increased risk of developing cardiotoxicity (HR=2.850; p=0.031). A history of hypertension was significantly associated withthe worsening of hypertension during ibrutinib therapy (HR=7.935; p=0.009). No significant associations were found between cardiotoxicity and other factors such as age, sex, number of prior treatment lines, clinical stage, or cytogenetic abnormalities.DiscussionThis study underscores the importance of cardiovascular monitoring in CLL patients undergoing ibrutinib therapy, particularly those with pre-existing cardiovascular conditions. These findings highlight the need for individualized treatment planning and close follow-up to mitigate the risk of cardiotoxicity and optimize patient outcomes.